At work with Grotowski on physical actions - Richards, Thomas, 1962- (Routledge, 1995)
At work with Grotowski on Physical Actions is a unique resource for actors and students - a compelling account of a decade's work with Jerzy Grotowski, one of the outstanding and most influential figures in twentieth century drama. Grotowski is inheritor of the mantle of Stanislavski; renowned and revered for his radical innovation as a director, and for his seminal manifesto Towards a Poor Theatre . This volume by Thomas Richards, his long-time collaborator, is the first available statement of Grotowski's current working practices and theoretical position.
Keywords: Grotowski, Jerzy, -- 1933-1999 -- Criticism and interpretation.; Grotowski, Jerzy, -- 1933-1999; Grotowski, Jerzy, -- 1933-1999 -- Critique et interpretation.; Grotowski, Jerzy, -- 1933-1999 -- Critique et interprétation.; Theater -- Production and direction.; Théâtre -- Production et mise en scène.; PERFORMING ARTS -- Theater -- Direction & Production.; Theater -- Production and direction; Lichamelijkheid.; Acteren.; Art dramatique.; Theatre -- Directing; Electronic books.; Criticism, interpretation, etc.